Efektivitas Penerapan Parkir Elektronik (E-Pakring) Dalam Pengelolaan Parkir Di Kota Samarinda - Clarissa Calcabilla; Budiman; Letizia Dyastari (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2023)
The results of the study show that the application of electronic parking (e-parking) in parking management in Samarinda city is not effective. This happens due to several problems regarding not achieving targets from predetermined locations, income targets not being achieved, people prefer cash payments because electronic parking is complicated and takes a long time, there are still illegal parking attendants, there are constraints from using EDC devices, namely the network which are less stable and machine errors, lack of socialization, lack of human resources, namely supervisory staff, optimization of public roadside parking levy revenue that does not reach the target. The inhibiting factors for the implementation of electronic parking (e-parking) in Samarinda City are the limited number of parking lots that are not proportional to the number of vehicles, low community technology capabilities, low community discipline, lack of public awareness to use non-cash payments and have e-money. To overcome these problems, the Samarinda City Transportation Service must carry out socialization to all target groups so that the overall goal is achieved properly.